A new cryptic species of the Aplastodiscus albosignatus group (Anura: Hylidae) - Pinheiro, Paulo D. P.; Pezzuti, Tiago L.; Berneck, Bianca V. M.; Lyra, Mariana L. [UNESP]; Lima, Raphael C. L.; Leite, Felipe S. F. (Deutsche Gesellschaft Herpetologie Terrarienkunde E V, 2021)
The genus Aplastodiscus currently includes 15 valid species, and a further five candidate species have already been pointed out in the literature. We here describe one of these candidate species, assigned to the A. albosignatus group, from the southeastern slopes of the Espinhaco Range, State of Minas Gerais, Brazil. The new species is cryptic with A. cavicola, being morphologically similar in both adult and larval stages. However, the two species are not sister taxa. The advertisement call of the new species is markedly distinct from all other known species of its genus. Examination of topotypic samples of A. cavicola corroborates the presence of this species in the Espinhaco Range, but also indicates the need for a revision of the taxonomic status of populations from the state of Rio de Janeiro assigned to this taxon.
Keywords: Amphibia; Anura; bioacoustics; conservation status; Neotropics; phylogeny; tadpoles; taxonomy; systematics